1973
DOI: 10.1002/1097-0142(197311)32:5<1256::aid-cncr2820320534>3.0.co;2-g
|View full text |Cite
|
Sign up to set email alerts
|

Carcinoma of the penis

Abstract: The prognosis of squamous carcinoma of the penis depends upon the stage of disease as determined by local invasion and involvement of inguinal nodes. Three-year survivals of 48 cases were: Stage I, 95%; Stage 11, 67%; Stage 111, 29%; and Stage IV, 0%. Most primary lesions were treated by partial penectomy, and no patient developed local recurrence. There was a significant discrepancy between initial clinical staging and histologic staging due to the difficulty in determining node metastases. In order to detect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0
16

Year Published

1977
1977
2009
2009

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 119 publications
(44 citation statements)
references
References 16 publications
0
28
0
16
Order By: Relevance
“…The prognosis for survival in patients with lymph node metastases is tightly correlated with the number and location of involved lymph nodes and the presence of extranodal extension [6]. …”
Section: Introductionmentioning
confidence: 99%
“…The prognosis for survival in patients with lymph node metastases is tightly correlated with the number and location of involved lymph nodes and the presence of extranodal extension [6]. …”
Section: Introductionmentioning
confidence: 99%
“…Survival-rate figures vary, but de Kernion et al (1973) found, in carcinoma arising de novo, a threeyear survival rate of 960% with stage 1 lesions (the stage in this case), and von Alth et al (1973) found a five-year survival rate of 84 % at the same stage.…”
Section: Discussionmentioning
confidence: 65%
“…Stage Ta or Tis tumours located on the distal prepuce can be cured by circumcision alone, if the surgeon ensures a wide safety margin (2 cm) free of tumour (Dekernion et al, 1973;Bissada, 1992). For stage Tis, Ta or T1 tumours we recommend an organ-preserving therapy.…”
Section: Treatment Of the Primary Lesionmentioning
confidence: 99%